Relationship between person-environment fit and academic achievement among undergraduate students in a Malaysian public university - Vahidighazvini, Naghmeh (2016)
In recent years despite the high budget allocating for education in Malaysia, the educational performance among students is low (Blueprint, 2013). Pascarella and Terenzini (2005; 1991) have identified four theories and models that affect on students academic achievement: (a) psychosocial, (b) cognitive-structural, (c) typological, and (d) person-environment interaction. This study is focused on person-environment interaction. The interactionist theory emphasized that neither personal characteristics nor situational factors alone could determine the responses or attitudes of individuals, but rather the interaction of these two was most important (Schneider, 1982; Terborg, 1981). Person-environment fit discussions were started by interactionists who believed that certain attitudes, cognitions, and behaviours are the outcomes of the interaction between the person and situational factors (Chatman, 1989; Muchinsky & Monahan, 1987; Ostroff & Schulte, 2007). Academic major satisfaction and academic achievement are two outcomes for person–environment (P–E) fit that use in this study. This study is used different types of P-E fit such as need supply major fit, demand ability major fit, objective and perceived interest major fit. The main aim of the present study was to examine the relationship between P-E fit on academic achievement, between P-E fit on academic satisfaction, and also the mediating effect of academic major satisfaction in relationship between P-E Fit and academic achievement. The present study is carried out in UPM. The population size of the study were 2503 undergraduate students of 12 faculties at UPM. The sample size for data analysis was 433. 385 students of 433 students replied the questions completely. After collecting the actual data, SPSS 20 and AMOS 22 software are used to analyze the obtained data. Findings for relationship between P-E fit and academic achievement have shown that there is a positive significant relationship between need supply major fit, demand ability major fit, perceived interest major fit with academic achievement, but there is not any significant relationship between objective interest major fit with academic achievement. Results for relationship between academic major satisfaction with academic achievement, and for relationship between P-E with major satisfaction was significant. Mediation analysis shows that major satisfaction partially mediate the relationship between demand ability major fit, need supply major fit, perceived interest major fit with academic achievement, but it fully mediate the relationship between objective interest major fit and academic achievement. This study has shown the importance role of academic major satisfaction for academic achievement especially for objective interest major fit as there is not relationship between objective interest major fit with academic achievement but major satisfaction can fully mediate this relationship.